Relationship between Long Duration Use of Hormonal Contraceptive and Serum Lipid Profiles among the Women of Dhaka City - Khatun, Kashefa; Nahar, Shamsun; Sultana, Abida; Chisty, Shahnur; Shahid, Asma Rumanaz; Arselan, Iqbal (Journal of Current and Advance Medical Research, 2019)
Background: Long duration use of hormonal contraceptives can cause different metabolic effects. Objective: The purpose for the present study was to see the relationship between long duration of use of hormonal contraceptives and serum lipid profiles. Methodology: This cross-sectional study was carried out in the Department of Obstetrics & Gynaecology in collaboration with the Biochemistry Department at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2004 to December 2005 for eighteen (18) months. Women of reproductive age group who had given the history of taking low-dose oral contraceptive pills (OCP) containing 30 meg ethinyloestradiol (EE) plus 150 meg levonorgestrel (LNG) were included as study population. The women were divided into group A which was consisted of women who were using OCP for up to 5 years and group B who were using OCP for more than 5 years. Blood was collected from each woman in fasting state and serum was sent for estimation of serum lipids profiles like serum triglycerides, total cholesterol, LDL and HDL. Result: The women in group A was consisted of 20 women and the rest 20 women were in group B. Comparison of mean age between control and case groups showed no significant difference (31.75±4.85 vs 30.43±5.44 years). In women using OCP ≤5 years and >5 years, the mean (±SD) cholesterol levels were 252.50±48.86 and 239.55±48.73 mg/dl (p>0.10), triglyceride levels were 204.30±48.10 and 191.45±67.89 mg/dL (p>0.10), HDL levels were 42.82±8.96 and 43.00±6.46 (p>0.10) and LDL levels were 168.83±50.82 and 158.26±50.32 (p>0.10) respectively. Conclusion: The level of total cholesterol and triglycerides are not significantly varied with long duration (more than 5 years) of oral contraceptive pills use. Journal of Current and Advance Medical Research 2019;6(1):10-13